"Thresholds" of the anthology: authorship and gender in the poetics by Ernestina de Champourcin and Josefina de la Torre - Fernández Menéndez, Raquel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The objective of this article is to analyze the poetics composed by Spanish women writers that are included in poetry anthologies in the 20th century. These paratexts, in which the authors describe their ideas about poetic creation, are fundamental for the comprehension of the anthology as a book and they constitute a key document for the self-representation of Spanish women writers. For that purpose, I recur to recent works developed around the question of the author in the francophone context, with the works of Jose-Luis Diaz, Dominique Maingueneau, Jérôme Meizoz or Ruth Amossy at the forefront, and to the feminist literary theory that during decades has been focused on the relationship between gender and authorship. Finally, I study from this point of view the poetics by Ernestina de Champourcin and Josefina de la Torre included in Poesía española. Antología (Los contemporáneos) (1934) by Gerardo Diego.
Keywords: Authorship; Gender Studies; Spanish Poetry; Spanish Contemporary Literature; Anthologies; Ernestina de Champourcin; Josefina de la Torre